Fluororesin film for battery exterior body, battery exterior body, and secondary battery
By using the heat-treated fluororesin film, the lack of electrolyte permeability and metal layer adhesion of the exterior body of the lithium-ion secondary battery is solved, and higher electrolyte permeability and adhesion are achieved. Improves battery stability and manufacturing process reliability.
Patent Information
- Application Number
- CN202380050626.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-07-05
- Publication Date
- 2025-02-14
AI Technical Summary
The exterior body of the conventional lithium-ion secondary battery has shortcomings in high electrolyte permeability and adhesion of the metal layer, which leads to battery deterioration and peeling problems during the manufacturing process.
The fluororesin film heat treated by 180°C was used. The surface oxygen element ratio reached more than 1.35 atomic % in XPS/ESCA measurement, and the absolute value of the MD and TD size change rate when cooling after heat treatment was controlled below 2%, so as to Improve adhesion and electrolyte permeability.
Excellent adhesion to the metal layer and electrolyte permeability resistance are achieved, thereby reducing deterioration of the battery exterior body and adverse conditions in the manufacturing process.
Smart Images

Figure BDA0005214707060000321 
Figure BDA0005214707060000341 
Figure BDA0005214707060000361
Abstract
Description
Technical Field
[0001] The present disclosure relates to a fluororesin film for a battery exterior body, a battery exterior body, and a secondary battery. Background Art
[0002] In recent years, lithium ion secondary batteries have become increasingly important as secondary batteries used in various fields, and improvements in performance are also being sought.
[0003] As one of the improvements in performance, studies have been conducted on extending the life of batteries from many viewpoints. As one of the studies, studies have also been conducted on battery exterior bodies.
[0004] A general form of a lithium ion secondary battery is to house a main body, which is a sheet-like laminate, in a battery case. Among them, a battery case of a laminate type battery is generally composed of a laminate having a metal layer such as aluminum and a resin film (Patent Documents 1 and 2).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2000-268873
[0008] Patent Document 2: Japanese Patent Application Publication No. 2002-16712 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The present disclosure provides a fluororesin film for a battery exterior having excellent adhesion to a metal layer. The present disclosure also provides a battery exterior having excellent resistance to electrolyte permeation.
[0011] Means for solving problems
[0012] The present disclosure relates to a fluororesin film for a battery outer casing, which is a fluororesin film for a battery outer casing composed of a composition containing a fluororesin, characterized in that:
[0013] After the film was heat treated at 180° C. for 3 minutes, the oxygen ratio of the surface state of one or both surfaces was measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) and was found to be 1.35 atomic % or more.
[0014] When the film was heat-treated at 180° C. for 10 minutes and then cooled to 25° C. and measured, the absolute values of the dimensional change rates in MD and TD before and after the heat treatment were 2% or less.
[0015] The oxygen element ratio is preferably 1.5 atomic % or more.
[0016] The fluororesin film for a battery exterior body preferably contains tetrafluoroethylene-perfluoroalkylvinyl ether (PFA) or tetrafluoroethylene-hexafluoropropylene (FEP).
[0017] The fluororesin film for the battery outer casing preferably has an oxygen element ratio when the surface state of one side or both sides is measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) and an oxygen element ratio when the film is etched in the depth direction at an incident angle of 45° for 15 minutes by an argon cluster ion beam, and the difference is 1.0 atomic % or more.
[0018] The fluororesin film for a battery exterior body preferably has an adhesive strength of more than 30 N / m on one side or both sides when the films are bonded together on the same surface at 200°C.
[0019] The fluororesin film for a battery exterior body preferably has a bonding strength of 500 N / m or more when the aluminum foil and the fluororesin film are bonded to each other.
[0020] The electrolyte permeability of the fluororesin film for battery exterior body is preferably 50 g / m 2 ·Day or less.
[0021] The present disclosure also relates to a battery exterior body, characterized by comprising the above-mentioned fluororesin film and a metal layer.
[0022] The battery outer casing further comprises a layer other than the metal layer and the fluororesin film.
[0023] The layers other than the metal layer and the fluororesin film may be at least one selected from the group consisting of polyethylene, polypropylene, polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
[0024] In the battery exterior body, the fluororesin film is preferably provided on at least one surface in the thickness direction and exists at a position in contact with the electrolyte solution when the battery is manufactured.
[0025] In the battery exterior body, the metal layer is preferably made of aluminum.
[0026] In the battery exterior body, it is preferred that the bonding strength between the aluminum foil and the fluororesin film is 500 N / mm or more.
[0027] The present disclosure also relates to a secondary battery including the battery exterior body and an electrolyte solution.
[0028] In the secondary battery, it is preferable that the fluororesin film of the battery exterior body is present at a position in contact with an electrolyte solution.
[0029] Effects of the Invention
[0030] According to the present disclosure, a fluororesin film for a battery exterior body having excellent adhesion to a metal layer can be obtained. In addition, according to the present disclosure, a battery exterior body having excellent resistance to electrolyte permeation can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is an explanatory diagram schematically showing a glass vessel used when testing the electrolyte permeability of a fluororesin membrane. DETAILED DESCRIPTION
[0032] In existing laminated lithium-ion batteries, a laminated body formed by laminating a plurality of polypropylene (PP) films on the surface of a metal foil such as aluminum foil or SUS foil is often used as an outer packaging material. However, in such a laminated body, battery degradation caused by the high electrolyte permeability of the PP film has become a problem.
[0033] On the other hand, since the fluororesin film has excellent barrier properties to the electrolyte, the battery exterior body using the fluororesin film and the metal foil has excellent resistance to electrolyte permeation.
[0034] However, when laminated with metal foil, the fluororesin film is prone to wrinkles and has low adhesion to metal. Therefore, for example, during the manufacturing process, the fluororesin film layer and the metal layer are prone to peeling, causing process defects and sometimes failing to fully demonstrate the electrolyte permeability resistance of the fluororesin film.
[0035] In the present disclosure, by using a fluororesin film having particularly high adhesiveness as the fluororesin film, the fluororesin film can be suitably used for battery exterior bodies.
[0036] In the present disclosure, by using a fluororesin film having sufficient adhesiveness and having an oxygen element ratio of 1.35 atomic % or more when the surface state of the surface bonded to the metal foil is measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) after heat treatment at 180°C for 3 minutes, it is possible to produce the above-mentioned battery outer casing with excellent resistance to electrolyte permeation.
[0037] In addition, the fluororesin film disclosed herein has an absolute value of 2% or less of dimensional change rate in MD and TD before and after heat treatment when the film is cooled to 25°C after heat treatment for 10 minutes, so the shape of the rolled film does not change over time. As a result, wrinkles of the film are not generated (tightly rolled), and the adhesion with metal foil etc. can be improved.
[0038] As described above, it was found that a laminate composed of the fluororesin film of the present disclosure and a metal layer such as an aluminum foil has good interlayer adhesion and excellent resistance to electrolyte permeation, and thus the laminate can be suitably used as a battery exterior body.
[0039] Hereinafter, the present disclosure will be described in more detail.
[0040] The present disclosure relates to a fluororesin film for a battery outer casing. The fluororesin film for a battery outer casing is composed of a composition containing a fluororesin. The resin constituting the fluororesin film is not particularly limited as long as it is a polymer partially containing fluorine atoms.
[0041] Two or more polymers containing fluorine atoms in part may be used. The fluororesin may contain at least one functional group selected from a carbonyl-containing group (e.g., anhydride group, a group having a carbonyl group between carbon atoms of a hydrocarbon group, a carbonate group, a carboxyl group, a haloformyl group, an alkoxycarbonyl group, etc.), a hydroxyl group, an epoxy group, an amide group, an amino group, and an isocyanate group. In addition, the composition containing the fluororesin may also contain other resins, rubbers, additives, fillers, etc. other than the fluororesin.
[0042] There is no particular limitation on the method for introducing the above-mentioned functional groups, and for example, the functional groups can be introduced when manufacturing the fluororesin. In this case, the functional groups are selected from at least one of the groups consisting of monomers, chain transfer agents and polymerization initiators used during manufacturing. As the above-mentioned monomers, for example, itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc. can be cited. As chain transfer agents, for example, chain transfer agents from methanol, acetic acid, acetic anhydride, methyl acetate, ethylene glycol, propylene glycol, etc. can be cited. As polymerization initiators, for example, ammonium persulfate, potassium persulfate, di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, tert-butyl peroxyisopropyl carbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, etc. can be cited.
[0043] The fluororesin is more preferably a fluororesin that can be melt-molded, and examples thereof include tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), a copolymer having a chlorotrifluoroethylene (CTFE) unit (CTFE copolymer), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-ethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), chlorotrifluoroethylene-ethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF) and polyvinyl fluoride (PVF), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer (THV), tetrafluoroethylene-vinylidene fluoride copolymer, and the like.
[0044] Among these melt-moldable fluororesins, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers (PFA) and tetrafluoroethylene-hexafluoropropylene copolymers (FEP) are preferred, and tetrafluoroethylene-hexafluoropropylene copolymers (FEP) are particularly preferred.
[0045] By using the above-mentioned melt-moldable fluororesin, melt molding is possible, so the processing cost can be suppressed compared with the case of using PTFE. Furthermore, the adhesion when bonding with metal foil can be improved.
[0046] The glass transition temperature of the resin constituting the fluororesin film is preferably 40°C or higher. If it is 40°C or higher, for example, when the roll film is stored at room temperature, deformation at ambient temperature is less likely to occur, which is preferred. It is more preferably 60°C or higher, and even more preferably 80°C or higher. The upper limit is not particularly limited, but is preferably 200°C or lower, more preferably 160°C or lower, and even more preferably 120°C or lower from the perspective of adhesiveness.
[0047] As the above-mentioned FEP, there is no particular limitation, but a copolymer in which the molar ratio of TFE units to HFP units (TFE units / HFP units) is 70 / 30 or more and less than 99 / 1 is preferred. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 97 / 3 or less. If the TFE unit is too little, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease. FEP can be a copolymer consisting only of TFE and HFP, and is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and HFP are 0.1 mol% to 10 mol%, and the total of TFE units and HFP units is 90 mol% to 99.9 mol%. As monomers copolymerizable with TFE and HFP, alkyl perfluorovinyl ether derivatives can be cited. Other copolymerizable monomers include, for example, cyclic hydrocarbon monomers having an acid anhydride group, and examples of acid anhydride monomers include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc. The acid anhydride monomers may be used alone or in combination of two or more.
[0048] The melting point of the FEP is preferably 150 to 320° C., more preferably 200 to 300° C., and even more preferably 240 to 280° C. The melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0049] The MFR of the FEP is preferably 0.01 g / 10 min to 100 g / 10 min, more preferably 0.1 g / 10 min to 80 g / 10 min, further preferably 1 g / 10 min to 60 g / 10 min, and particularly preferably 1 g / 10 min to 50 g / 10 min. It should be noted that in this specification, MFR is a value measured under the conditions of a temperature of 372° C. and a load of 5.0 kg according to ASTM D3307.
[0050] As the above-mentioned PFA, there is no particular limitation, and a copolymer in which the molar ratio of TFE units to PAVE units (TFE units / PAVE units) is 70 / 30 or more and less than 99.5 / 0.5 is preferred. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.5 / 1.5 or less. If the TFE unit is too few, the mechanical properties tend to decrease; if it is too much, the melting point is too high and the moldability tends to decrease. The above-mentioned PFA can be a copolymer consisting only of TFE and PAVE, and is also preferably a copolymer in which the monomer units from monomers copolymerizable with TFE and PAVE are 0.1 mol% to 10 mol%, and the total of TFE units and PAVE units is 90 mol% to 99.9 mol%. As monomers copolymerizable with TFE and PAVE, HFP, CZ 3 Z 4 =CZ 5 (CF 2 ) n Z 6 (Where Z 3 , Z 4 and Z 5 are the same or different, representing a hydrogen atom or a fluorine atom, Z 6 represents a hydrogen atom, a fluorine atom or a chlorine atom, and n represents an integer of 2 to 10. The vinyl monomer represented by ) and CF 2 =CF-OCH 2 -Rf 7 (Where Rf 7 represents a perfluoroalkyl group having 1 to 5 carbon atoms. ) and the like. Other copolymerizable monomers include, for example, cyclic hydrocarbon monomers having an acid anhydride group, and examples of acid anhydride monomers include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, and the like. The acid anhydride monomers may be used alone or in combination of two or more.
[0051] The melting point of PFA is preferably 180 to 340° C., more preferably 230 to 330° C., and further preferably 280 to 320° C. The melting point is a temperature corresponding to a maximum value in a heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0052] The melt flow rate (MFR) of the PFA is preferably 0.1 g / 10 min to 100 g / 10 min, more preferably 0.5 g / 10 min to 90 g / 10 min, and even more preferably 1.0 g / 10 min to 85 g / 10 min.
[0053] As described above, fluororesins have a relatively high melting point and are therefore excellent in heat resistance, and can be suitably used as battery packaging materials.
[0054] In the present specification, the content of each monomer unit constituting the fluororesin can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the types of monomers.
[0055] The fluororesin film of the present disclosure may contain components other than the fluororesin.
[0056] The components that may be contained are not particularly limited, and examples thereof include fillers such as silica particles and glass short fibers, and fluorine-free thermosetting resins / thermoplastic resins. The content of components other than the fluororesin is not particularly limited, and for example, is preferably 5% by mass or more and 60% by mass or less in the fluororesin film. More preferably, it is 10% by mass or more and 40% by mass or less.
[0057] As mentioned above, fluororesins are generally raw materials that are difficult to obtain adhesion to metals. Therefore, in order to improve the lamination properties, it is preferred to perform surface treatment on the fluororesin film. Such surface treatment is generally known to be a method of mainly increasing the amount of oxygen atoms on the resin surface.
[0058] The effect of the surface treatment of the fluororesin film for improving such adhesion tends to be reduced by heating. It is speculated that this is because the oxygen atoms on the surface are detached by heating, and the amount of oxygen atoms on the surface is reduced. In the lamination process, in order to improve productivity, for example, lamination is sometimes performed after preheating at a temperature above the glass transition temperature and below the melting point. In this way, in order to ensure that the fluororesin film subjected to the thermal history has sufficient adhesion when bonding to the metal foil, the oxygen atom ratio when the surface bonded to the metal foil is measured using a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) after the film is heat treated at 180°C for 3 minutes must be 1.35 atomic % or more.
[0059] The fluororesin film disclosed herein has an oxygen element ratio of 1.35 atomic % or more when the surface state of one or both surfaces is measured by ESCA after heat treatment at 180° C. for 3 minutes. The oxygen atomic ratio is more preferably 1.5 atomic % or more, further preferably 1.8 atomic % or more, and most preferably 2.0 atomic % or more.
[0060] The heat treatment at 180° C. for 3 minutes is performed by placing the film on a metal tray and performing the treatment in an electric furnace under an air atmosphere.
[0061] The fluororesin film disclosed herein may be a fluororesin film having a surface state of one or both sides measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) and an oxygen element ratio measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) after etching the film in the depth direction for 15 minutes at an incident angle of 45° using an argon cluster ion beam, which is 1.0 atomic % or more. By increasing the oxygen element ratio of the surface that contributes to bonding in this way, sufficient bonding strength can be obtained without impairing resistance to electrolyte permeability.
[0062] When the fluororesin film of the present disclosure is heat-treated at 180°C for 10 minutes and then cooled to 25°C and measured, the absolute values of the dimensional changes in MD and TD before and after the heat treatment are 2% or less.
[0063] The dimensional change rate is more preferably 1.8% or less, and most preferably 1.5% or less.
[0064] In the present disclosure, regarding the dimensional change rate, marks are set at intervals of 180 mm in a film sample cut into 300 mm squares, and heat treatment is performed for 10 minutes without applying a load in an electric furnace set at 180°C in an air atmosphere. The film is then cooled to 25°C, and the mark intervals in the MD and TD directions of the cooled film are measured. The value is calculated from the change in the mark intervals before and after the heat treatment.
[0065] For example, one of the causes of defects in the lamination process is that if a rolled film is wrinkled (tightly rolled), it will be laminated in a wrinkled state during lamination. The reason for such wrinkles (tightly rolled) is that the shape of the rolled film changes over time.
[0066] It is believed that the change in the film shape over time is caused by the residual stress in the film, so it is necessary to suppress the change. As a method for suppressing the dimensional change, there can be cited: a method of annealing to relieve the residual stress in the fluororesin film; a method of adjusting the melt extrusion conditions such as the die lip opening of the T-die and the air gap or the film winding conditions in the film manufacturing process to make it difficult for the residual stress to remain; etc.
[0067] The fluororesin film disclosed herein preferably has an adhesive strength of more than 30 N / m when the films are bonded to each other on the same surface at 200° C. on only one side or on both sides. By having such an adhesive strength, even after the fluororesin film is heat-treated, the adhesiveness when used in combination with various other substrates is excellent. The above-mentioned adhesive strength is more preferably more than 50 N / m, and further preferably more than 100 N / m.
[0068] The fluororesin film preferably has a bonding strength of 500 N / m or more when, for example, an aluminum foil and the fluororesin film are bonded to each other.
[0069] Specifically, for example, the bonding strength when bonded to the aluminum foil using a heat sealer under the conditions of a temperature of 320°C, a pressure of 1.5 MP, and a time of 100 to 300 seconds is preferably 500 N / m or more, more preferably 700 N / m or more, further preferably 900 N / m or more, and most preferably 1000 N / m or more. The bonding strength herein refers to the bonding strength measured under the conditions described in the examples for the laminate bonded under the above conditions.
[0070] By having such an adhesive strength, the adhesiveness with the metal layer is excellent, and when it is used as a battery exterior material, it can be made excellent in the adhesion between layers and excellent in the resistance to electrolyte permeation.
[0071] The electrolyte permeability of the fluororesist membrane disclosed in the present invention is preferably 50 g / m 2 ·day or less. More preferably 30g / m 2 ·Day or less, more preferably 20g / m 2 The electrolyte permeability refers to the electrolyte permeability measured under the conditions described in the Examples.
[0072] The fluororesin film of the present disclosure can be used as a film for a battery exterior body by laminating with other substrates.
[0073] The thickness of the fluororesin film disclosed herein is more preferably 5 μm to 500 μm, and further preferably 12.5 μm to 150 μm. The thickness within the above range can reduce the thickness of the laminate while maintaining resistance to electrolyte permeation, which is related to miniaturization of the battery when used as an outer casing of the battery.
[0074] (Method for producing fluororesin film)
[0075] Hereinafter, an example of the method for producing the fluororesin film of the present disclosure will be described in detail. It should be noted that the fluororesin film of the present disclosure is not limited to being produced by the following production method.
[0076] The fluororesin film disclosed in the present invention is not particularly limited to the molding method when it is made into a film state, and examples thereof include a method of melt molding such as extrusion molding; a method of using a casting method based on preparing a solution or dispersion containing a fluororesin, applying it to a substrate and drying it; etc. Furthermore, the film may be stretched by a uniaxial stretching method or a biaxial stretching method, or may be an unstretched film.
[0077] The fluororesin film obtained by such a method can be made into a fluororesin film satisfying the above-mentioned conditions by subjecting one or both sides of the fluororesin film to surface treatment and annealing treatment under appropriate conditions.
[0078] In order to obtain a fluororesin film satisfying the above-mentioned properties, the treatment process conditions after the fluororesin film is formed are important. As described above, an example of a method for reducing the shrinkage rate in order to achieve the object of the present disclosure is annealing.
[0079] The annealing treatment of the fluororesin film is usually a heat treatment. Therefore, when the annealing treatment is performed after the surface treatment, the oxygen atomic weight is reduced, resulting in a reduction in bonding ability. In addition, since the bonding ability is reduced due to the preheating process during lamination, when the annealing treatment is performed, appropriate conditions need to be selected as conditions for the surface treatment and the annealing treatment. In addition, in order to avoid problems caused by such an annealing treatment, methods such as reducing internal stress by adjusting the manufacturing process of the film can also be adopted.
[0080] In the present disclosure, by adjusting the above-mentioned various conditions and producing a fluororesin film satisfying the above-mentioned conditions, it is possible to reduce defects during lamination and obtain good adhesiveness.
[0081] The specific method of the surface modification is not particularly limited, and the surface modification can be performed by any known method.
[0082] The surface modification of the fluororesin film can be carried out by a discharge treatment based on corona discharge treatment, glow discharge treatment, plasma discharge treatment, sputtering treatment, etc., which has been carried out in the past. For example, in addition to controlling the surface free energy by introducing oxygen, nitrogen, hydrogen, etc. into the discharge atmosphere, the surface to be modified is exposed to an atmosphere of an inert gas containing an organic compound as an inert gas containing an organic compound, and a high-frequency voltage is applied between electrodes to generate a discharge, thereby generating active species on the surface, and then introducing functional groups of organic compounds or graft-polymerized organic compounds, thereby surface modification can be carried out. Examples of the above-mentioned inert gas include nitrogen, helium, argon, etc.
[0083] Examples of the organic compound in the above-mentioned inert gas containing organic compounds include polymerizable or non-polymerizable organic compounds containing oxygen atoms, such as vinyl esters such as vinyl acetate and vinyl formate; acrylic esters such as glycidyl methacrylate; ethers such as vinyl ethyl ether, vinyl methyl ether, and glycidyl methyl ether; carboxylic acids such as acetic acid and formic acid; alcohols such as methanol, ethanol, phenol, and ethylene glycol; ketones such as acetone and methyl ethyl ketone; carboxylic acid esters such as ethyl acetate and ethyl formate; acrylic acids such as acrylic acid and methacrylic acid, etc. Among these, vinyl esters, acrylic esters, and ketones are preferred, and vinyl acetate and glycidyl methacrylate are particularly preferred, from the viewpoint that the surface after modification is not easily deactivated, that is, the life is long, and the viewpoint that it is easy to handle in terms of safety.
[0084] The concentration of the organic compound in the above-mentioned inert gas containing organic compounds varies depending on the type of the organic compound, the type of fluororesin to be surface-modified, etc., and is usually 0.1 volume % to 3.0 volume %, preferably 0.1 volume % to 1.0 volume %, more preferably 0.15 volume % to 1.0 volume %, and further preferably 0.30 volume % to 1.0 volume %. The discharge conditions can be appropriately selected according to the degree of surface modification as the target, the type of fluororesin, the type or concentration of the organic compound, etc. Usually, when the discharge amount is 50W·min / m 2 ~1500W·min / m 2 , preferably 70W·min / m 2 Above 1400W·min / m 2 The discharge treatment is carried out within the following range. The treatment temperature can be carried out at any temperature in the range of more than 0°C and less than 100°C. Due to concerns about elongation, wrinkles, etc. of the film, it is preferably below 80°C. Regarding the degree of surface modification, considering that the adhesion of the surface is reduced due to heat during post-processing, the presence ratio of oxygen element when observed by ESCA is more than 2.6%, preferably more than 2.8%, more preferably more than 3.0%, and further preferably more than 3.5%. There is no particular provision about the upper limit, but in view of the impact on productivity and other physical properties, it is preferably less than 25.0%. There is no particular provision for the presence ratio of nitrogen element, but it is preferably more than 0.1%.
[0085] In the manufacture of the fluororesin film disclosed herein, it is preferred to perform annealing after the above-mentioned surface treatment. In addition, sometimes heat treatment is performed in the process of laminating the film with other materials such as metal foil. Therefore, by undergoing these heat treatments, the amount of oxygen on the surface of the fluororesin film is reduced. Thus, it is preferred to perform surface modification under the condition of obtaining sufficient amount of surface oxygen when the fluororesin film is actually bonded with other materials such as metal foil.
[0086] (Annealing treatment)
[0087] The annealing treatment can be performed by heat treatment. The heat treatment can be performed, for example, by passing the roll-to-roll through a heating furnace.
[0088] The annealing temperature is preferably above the glass transition temperature -20 ° C and below the melting point, more preferably above the glass transition temperature and below the melting point -20 ° C, and further preferably above the glass transition temperature and below the melting point -60 ° C. The annealing time is not particularly limited, and can be appropriately adjusted in, for example, 0.5 minutes to 60 minutes. In addition, if the film after passing through the annealing furnace contacts the roller of the winding device at high temperature, it is easy to cause the film to deform (undulate) due to the thermal contraction caused by temperature changes. In order to prevent this situation, it is also possible to pass through a cooling zone after the high-temperature annealing zone, thereby cooling the film and then winding it up using a winding device. There is no particular limitation on the cooling method, and cooling can be performed with cold air, cooling rollers, etc., and the film temperature is preferably set to be lower than the glass transition temperature.
[0089] When heating in the roll-to-roll manner, the tension can be appropriately adjusted according to the film thickness, set temperature, etc., and is preferably 20 N / m or less. By heating under such conditions, internal stress can be fully relaxed and dimensional changes will not occur, which is preferred.
[0090] The order of the surface treatment and annealing treatment is not particularly limited, and the number of times each process is performed is not limited to one time, and it can also be performed more than two times. Since tension is applied in the surface treatment process, it is preferred to perform annealing after the surface treatment from the perspective of controlling the thermal shrinkage rate. In addition, it is also possible to cut into a specified width and length before or after these treatments. In this case, it is preferred to adjust the tension so that the film does not stretch.
[0091] As described above, in the present disclosure, by adjusting the above-mentioned various conditions, a fluororesin film satisfying the above-mentioned conditions is prepared, and a film having good adhesiveness while reducing inconvenience during lamination is prepared.
[0092] <Battery exterior>
[0093] The present disclosure also relates to a battery exterior body comprising the above-mentioned fluororesin film and a metal layer.
[0094] The battery casing houses the battery element including the positive electrode, the negative electrode and the electrolyte solution, and protects the battery from external impact, environmental degradation and the like when the battery is in use.
[0095] The battery exterior body of the present disclosure has a layer structure including the above-mentioned fluororesin film and the metal layer.
[0096] In particular, the battery exterior body of the present disclosure is suitable for use in a laminated battery. The battery exterior body of the present disclosure is excellent in resistance to electrolyte permeation.
[0097] Examples of the metal layer include metal foils such as aluminum (Al) and stainless steel (SUS), among which aluminum (Al) foil is preferred.
[0098] The thickness of the metal layer is not particularly limited, but is preferably in the range of 1 μm to 100 μm, more preferably in the range of 5 μm to 50 μm, and further preferably in the range of 9 μm to 40 μm. By having a thickness in the above range, the thickness of the laminate can be made thinner while maintaining resistance to electrolyte permeability, which is related to the miniaturization of the battery when used as an outer casing of the battery.
[0099] In the battery exterior body of the present disclosure, as described above, the fluororesin film of the present disclosure has excellent adhesion to the metal layer and is therefore preferably used for a layer that is in direct contact with the metal layer.
[0100] In the battery exterior body, for example, it is preferred that the bonding strength between the aluminum foil and the fluororesin film is 500 N / m or more.
[0101] Specifically, for example, the bonding strength when bonding to aluminum foil using a heat sealer under the conditions of a temperature of 320°C, a pressure of 1.5 MP, and a time of 100 to 300 seconds is preferably 500 N / m or more, more preferably 700 N / m or more, further preferably 900 N / m or more, and most preferably 1000 N / m or more.
[0102] The adhesive strength herein refers to the adhesive strength measured under the conditions described in Examples with respect to a laminate bonded under the above conditions.
[0103] The battery exterior body of the present disclosure may further include layers other than the above-mentioned metal layer and fluororesin film.
[0104] Examples of layers other than the metal layer and the fluororesin film include films composed of at least one selected from the group consisting of polyethylene, polypropylene, polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
[0105] The fluororesin film of the present disclosure also has good adhesion to the above-mentioned resins.
[0106] The thickness of the film other than the fluororesin film is not particularly limited, but is preferably in the range of 1 μm to 100 μm, more preferably in the range of 5 μm to 50 μm, and even more preferably in the range of 9 μm to 35 μm.
[0107] The layer structure of the battery casing of the present disclosure is not particularly limited and may be appropriately set according to the purpose. Examples of laminated battery casings include battery casings having a sealed structure formed by heat-fusion bonding resin layers when the battery is manufactured.
[0108] Such a battery exterior body is preferably composed of, for example, an outer layer film / metal layer / inner layer film. The outer layer film and the inner layer film may each be a single-layer film or a multilayer film in which a plurality of films of the same or different types are stacked.
[0109] As described above, the fluororesin film of the present disclosure has excellent adhesion to the metal layer, and therefore is preferably configured to be in direct contact with the metal layer.
[0110] The battery exterior body of the present disclosure preferably has the fluororesin film provided on at least one surface in the thickness direction, and is present at a position in contact with the electrolyte solution when the battery is manufactured.
[0111] The fluororesin film disclosed herein is stable to electrolyte and has excellent heat sealability, and therefore can be suitably used as the innermost layer of a battery exterior body. By forming the innermost layer in contact with the electrolyte, the effect of resistance to electrolyte permeation is further exerted.
[0112] The method of compounding the metal foil, fluororesin film, etc. is not particularly limited, and examples thereof include a method of laminating using a metal layer, a preformed fluororesin film, etc. by a roll-to-roll process and applying pressure under heating with a press.
[0113] The fluororesin film of the present disclosure has the effect of causing few defects during lamination and also achieving good adhesion with metal foil, and thus can provide a laminate that can be suitably used for a battery exterior body.
[0114] In particular, even when the resin layer is thermally welded via the current collecting terminal to form a sealed structure, the metal and the resin can be joined well.
[0115] The battery outer casing may be formed appropriately according to the form of the battery to be produced, for example, by cutting into a desired size or forming (deep drawing, bulging, etc.) to obtain a molded case.
[0116] The present disclosure also relates to a secondary battery including the battery exterior body and an electrolyte solution.
[0117] Examples of the secondary battery include alkali metal or alkaline earth metal secondary batteries, and specifically, lithium ion secondary batteries, lithium metal secondary batteries, sodium batteries, and calcium batteries.
[0118] In addition, as the shape of the secondary battery, there are a laminate type, a cylindrical shape, a square shape, a needle shape, and the like.
[0119] In particular, a laminated lithium ion secondary battery is preferred.
[0120] The secondary battery of the present disclosure can use the negative electrode, positive electrode, electrolyte solution, separator, etc. used in a known secondary battery. These will be described in detail below.
[0121] <Negative electrode>
[0122] In the secondary battery of the present disclosure, the negative electrode is preferably composed of a negative electrode active material layer containing a negative electrode active material and a current collector.
[0123] The negative electrode contains graphite, a silicon-based material, a tin-based material, or a metal composite oxide material containing an alkali metal.
[0124] More specifically, the negative electrode active material is any one of the thermal decomposition products of organic matter under various thermal decomposition conditions or carbonaceous materials such as artificial graphite and natural graphite that can absorb / release alkali metals; silicon-based materials and tin-based materials such as tin oxide and silicon oxide that can absorb / release alkali metals; and metal composite oxide materials containing alkali metals. Two or more of these negative electrode active materials can be used in combination.
[0125] As a carbonaceous material capable of absorbing / releasing alkali metals, it is preferred that artificial graphite or refined natural graphite is manufactured by high-temperature treatment of graphitizable pitch obtained from various raw materials, or a material obtained by carbonizing these graphites after surface treatment with organic matter such as pitch; due to the good balance between the initial irreversible capacity and the high current density charge and discharge characteristics, it is more preferred to be selected from the following materials: natural graphite; artificial graphite; carbonaceous materials obtained by heat-treating artificial carbonaceous materials and artificial graphite materials at a range of 400°C to 3200°C for more than one time; a carbonaceous material in which the negative electrode active material layer contains at least two or more carbonaceous materials with different crystallinity and / or a contact interface with the carbonaceous materials with said different crystallinity; a carbonaceous material in which the negative electrode active material layer has at least two or more carbonaceous materials with different orientations. In addition, these carbon materials can be used alone or in any combination and proportion.
[0126] Examples of the carbonaceous materials obtained by heat-treating the artificial carbonaceous material and the artificial graphite material at a temperature in the range of 400°C to 3200°C for more than one time include coal-based coke, petroleum-based coke, coal-based asphalt, petroleum-based asphalt and materials obtained by oxidation treatment of these asphalts, needle coke, asphalt coke and carbon agents obtained by partially graphitizing them, furnace black, acetylene black, asphalt-based carbon fibers and other organic materials thermal decomposition products, carbonizable organic materials and their carbides, or solutions obtained by dissolving carbonizable organic materials in low molecular weight organic solvents such as benzene, toluene, xylene, quinoline, n-hexane and their carbides, etc.
[0127] Specific examples of silicon-based materials and tin-based materials include simple Si, SiB 4 、SiB 6 Mg 2 Si、Ni 2Si, TiSi 2 , MoSi 2 , CoSi 2 , NiSi 2 , CaSi 2 , CrSi 2 , Cu 6 Si, FeSi 2 , MnSi 2 , NbSi 2 , TaSi 2 , VSi 2 , WSi 2 , ZnSi 2 , SiC, Si 3 N 4 , Si 2 N 2 O, SiO v (0 < v ≤ 2), LiSiO or elemental tin, SnSiO 3 , LiSnO, Mg 2 , Sn, SnO w (0 < w ≤ 2), etc.
[0128] In addition, composite materials can be cited in which Si or Sn is used as the first constituent element and which further contain second and third constituent elements. The second constituent element is, for example, at least one selected from the group consisting of cobalt, iron, magnesium, titanium, vanadium, chromium, manganese, nickel, copper, zinc, gallium, and zirconium. The third constituent element is, for example, at least one selected from the group consisting of boron, carbon, aluminum, and phosphorus.
[0129] In particular, from the aspect of obtaining a high battery capacity and excellent battery characteristics, as the above metal material, elemental silicon or tin (which may contain trace impurities), SiO v (0 < v ≤ 2), SnO w (0 ≤ w ≤ 2), Si-Co-C composite materials, Si-Ni-C composite materials, Sn-Co-C composite materials, Sn-Ni-C composite materials, etc. are preferred.
[0130] As the alkali metal-containing metal composite oxide material used as the negative electrode active material, there is no particular limitation as long as it can occlude / release alkali metal. From the aspect of high current density charge / discharge characteristics, a material containing titanium and an alkali metal is preferred, a composite metal oxide material containing an alkali metal and titanium is more preferred, and a composite oxide of an alkali metal and titanium (hereinafter, simply referred to as "alkali metal titanium composite oxide") is further preferred. That is, if an alkali metal titanium composite oxide having a spinel structure is used as the negative electrode active material in an electrolyte battery, the output resistance is greatly reduced, so it is particularly preferred.
[0131] The alkali metal titanium composite oxide is preferably of the general formula:
[0132] Mq 8 rO 4
[0133] [wherein, M is at least one metal selected from the group consisting of Li, Na and K; M 8 represents at least one element selected from the group consisting of Na, K, Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb. ] is a compound shown.
[0134] Among the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.
[0135] In the above composition,
[0136] (i)1.2≤p≤1.4, 1.5≤q≤1.7, r=0
[0137] (ii)0.9≤p≤1.1, 1.9≤q≤2.1, r=0
[0138] (iii) A compound in which 0.7≤p≤0.9, 2.1≤q≤2.3, and r=0 is particularly preferred because the battery performance is well balanced.
[0139] Regarding the particularly preferred composition of the above compound, (i) M 4 / 3 Ti 5 / 3 O 4 , (ii) is M 1 Ti 2 O 4 , (iii) is M 4 / 5 Ti 11 / 5 O 4 In addition, regarding the structure where r≠0, for example, M 4 / 3 Ti 4 / 3 Al 1 / 3 O 4 As a preferred structure.
[0140] The negative electrode mixture preferably further includes a binder, a thickener, and a conductive material.
[0141] As the above-mentioned binder, any substance can be used as long as it is a material safe for the solvent and electrolyte used in electrode manufacturing, and examples thereof include: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, chitosan, alginic acid, polyacrylic acid, polyimide, cellulose, and nitrocellulose; rubber polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers. or its hydrogenated product; thermoplastic elastomer polymers such as EPDM (ethylene propylene diene terpolymer), styrene ethylene butadiene styrene copolymer, styrene isoprene styrene block copolymer or its hydrogenated product; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene vinyl acetate copolymer, propylene α-olefin copolymer; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride copolymer, tetrafluoroethylene ethylene copolymer; polymer compositions having ion conductivity of alkali metal ions (particularly lithium ions), etc. These may be used alone or in any combination and ratio.
[0142] The ratio of the binder to the negative electrode active material is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 0.6% by mass or more, and preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, particularly preferably 8% by mass or less. If the ratio of the binder to the negative electrode active material is higher than the above range, the ratio of the binder that does not help the battery capacity increases, and there is a situation where the battery capacity is reduced. In addition, if it is lower than the above range, it sometimes leads to a reduction in the strength of the negative electrode.
[0143] In particular, when the main component contains a rubber-like polymer represented by SBR, the ratio of the binder to the negative electrode active material is usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 0.6% by mass or more, and usually 5% by mass or less, preferably 3% by mass or less, and more preferably 2% by mass or less. In addition, when the main component contains a fluorine-based polymer represented by polyvinylidene fluoride, the ratio relative to the negative electrode active material is usually 1% by mass or more, preferably 2% by mass or more, and more preferably 3% by mass or more, and usually 15% by mass or less, preferably 10% by mass or less, and more preferably 8% by mass or less.
[0144] Examples of the thickener include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, polyvinyl pyrrolidone, and salts thereof. One type may be used alone, or two or more types may be used in any combination and ratio.
[0145] The ratio of thickener to negative electrode active material is usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 0.6% by mass or more, and usually 5% by mass or less, preferably 3% by mass or less, more preferably 2% by mass or less. If the ratio of thickener to negative electrode active material is lower than the above range, the coating property is sometimes significantly reduced. In addition, if it is higher than the above range, the proportion of negative electrode active material in the negative electrode active material layer is reduced, and sometimes the problem of reduced battery capacity or increased resistance between negative electrode active materials occurs.
[0146] As the above-mentioned conductive material, any known conductive material can be used. As specific examples, metal materials such as copper and nickel, graphite (graphite) such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, needle coke, carbon nanotubes, fullerene, carbon materials such as amorphous carbon such as VGCF, etc. can be cited. It should be noted that they can be used alone or in any combination and ratio. Two or more kinds can be used together.
[0147] The conductive material is used in a manner that it is usually contained in the negative electrode active material layer in an amount of 0.01 mass % or more, preferably 0.1 mass % or more, more preferably 1 mass % or more, and usually contained in an amount of 50 mass % or less, preferably 30 mass % or less, more preferably 15 mass % or less. If the content is below this range, the conductivity may be insufficient. On the contrary, if the content is above this range, the battery capacity may be reduced.
[0148] The type of solvent used to form the slurry is not particularly limited as long as it can dissolve or disperse the negative electrode active material, the binder, and, if necessary, the thickener and the conductive material. Both aqueous solvents and organic solvents can be used.
[0149] Examples of aqueous solvents include water and alcohols, and examples of organic solvents include N-methylpyrrolidone (NMP), dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N,N-dimethylaminopropylamine, tetrahydrofuran (THF), toluene, acetone, diethyl ether, dimethylacetamide, hexamethylphosphoramide, dimethyl sulfoxide, benzene, xylene, quinoline, pyridine, methylnaphthalene, hexane, and the like.
[0150] The amount of the solvent to be blended is determined in consideration of coating properties on a current collector, thin film forming properties after drying, etc. The ratio of the binder to the solvent is preferably 0.5:99.5 to 20:80 in terms of mass ratio.
[0151] In order to further improve the adhesion to the collector, the negative electrode active material layer may further include acrylic resins such as polymethacrylate and polymethyl methacrylate, polyimide, polyamide and polyamide-imide resins. In addition, a crosslinking agent may be added to form a crosslinked structure by irradiating radiation such as gamma rays and electron beams. The crosslinking treatment method is not limited to radiation irradiation, and other crosslinking methods may be used, such as adding an amine-containing compound that can be thermally crosslinked, a cyanurate-containing compound, etc. to perform thermal crosslinking.
[0152] In order to improve the dispersion stability of the slurry, a dispersant such as a resin, a cationic surfactant, a nonionic surfactant, etc. having a surface active effect may be added.
[0153] The material of the negative electrode current collector includes metals such as copper, nickel, titanium, tantalum, stainless steel, or alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials are preferred, and copper, nickel, or alloys thereof are particularly preferred.
[0154] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal film, metal sheet, stamping metal, foamed metal, etc. can be enumerated, and in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be enumerated. Among these, preferred metal film. It should be noted that the film can be suitably formed into a mesh.
[0155] The thickness of the film is arbitrary, usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the film is thinner than this range, the strength required as a current collector is sometimes insufficient. On the contrary, if the film is thicker than this range, the handling property is sometimes impaired.
[0156] The manufacture of the negative electrode can be carried out according to conventional methods. For example, a method can be cited in which the above-mentioned binder, thickener, conductive material, solvent, etc. are added to the above-mentioned negative electrode material to form a slurry, applied to the collector, and pressed after drying to achieve high density. In addition, in the case of using an alloy material, a method of forming a thin film layer (negative electrode active material layer) containing the above-mentioned negative electrode active material by a method such as a vapor deposition method, a sputtering method, a plating method, etc. is also used.
[0157] The electrode structure when the negative electrode active material is electrically polarized is not particularly limited. The density of the negative electrode active material on the current collector is preferably 1 g·cm -3More preferably, 1.2 g·cm -3 More than 1.3 g·cm -3 More than, and preferably 2.2 g·cm -3 Below, more preferably 2.1 g·cm -3 Below, more preferably 2.0 g·cm -3 Below, particularly preferably 1.9 g·cm -3 If the density of the negative electrode active material on the collector is higher than the above range, the negative electrode active material particles are destroyed, which sometimes leads to an increase in the initial irreversible capacity and a deterioration in the high current density charge and discharge characteristics caused by a decrease in the permeability of the electrolyte to the collector / negative electrode active material interface. In addition, if it is lower than the above range, sometimes the conductivity between the negative electrode active materials decreases, the battery resistance increases, and the capacity per unit volume decreases.
[0158] The thickness of the negative electrode plate is designed according to the positive electrode plate used and is not particularly limited. The thickness of the composite layer obtained by subtracting the thickness of the metal foil of the core material is usually 15 μm or more, preferably 20 μm or more, more preferably 30 μm or more, and usually 300 μm or less, preferably 280 μm or less, more preferably 250 μm or less.
[0159] The ratio of the thickness of the current collector to the negative electrode active material layer is not particularly limited, and the value of (the thickness of the negative electrode active material layer on one side before the electrolyte is injected) / (the thickness of the current collector) is preferably less than 20, more preferably less than 15, and most preferably less than 10, and preferably more than 0.5, more preferably more than 0.8, and most preferably more than 1. If it is higher than this range, the current collector sometimes generates heat caused by Joule heat during high current density charging and discharging. If it is lower than this range, the volume ratio of the current collector to the negative electrode active material increases, and the capacity of the battery sometimes decreases.
[0160] In addition, a negative electrode plate having a substance with a different composition attached to the surface of the negative electrode plate may also be used. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; and the like.
[0161] <Positive electrode>
[0162] In the secondary battery of the present disclosure, the positive electrode is preferably composed of a positive electrode active material layer containing a positive electrode active material and a current collector.
[0163] As the above-mentioned positive electrode active material, there is no particular limitation as long as it can electrochemically contain / release alkali metal ions, for example, preferably a material containing an alkali metal and at least one transition metal. As specific examples, transition metal composite oxides containing alkali metals, transition metal phosphate compounds containing alkali metals, sulfur-based materials, conductive polymers, etc. can be cited.
[0164] Among them, as the positive electrode active material, a transition metal composite oxide containing an alkali metal that can generate a high voltage is particularly preferred. As the above-mentioned alkali metal ion, lithium ion, sodium ion, potassium ion, etc. can be cited. In a preferred embodiment, the alkali metal ion can be a lithium ion. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.
[0165] Examples of the alkali metal-containing transition metal composite oxide include
[0166] Formula: M a Mn 2-b M 1 b O 4
[0167] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0.9≤a; 0≤b≤1.5; M 1 A lithium-manganese spinel composite oxide represented by at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge,
[0168] Formula: MNi 1-c M 2 cO 2
[0169] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0≤c≤0.5; M 2 A lithium-nickel composite oxide represented by at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, or
[0170] Formula: MCo 1-d M 3 d O 2
[0171] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0≤d≤0.5; M 3is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge)
[0172] The lithium-cobalt composite oxide shown.
[0173] Among the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.
[0174] Among them, MCoO is preferred from the perspective of providing a secondary battery with high energy density and high output. 2 MMnO 2 、MNiO 2 MMn 2 O 4 、MNi 0.8 Co 0.15 Al 0.05 O 2 , or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 etc., and preferably the compound represented by the following general formula (3).
[0175] MNi h Co i Mn j M 5 k O 2 (3)
[0176] (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, (h+i+j+k)=1.0, 0≤h≤1.0, 0≤i≤1.0, 0≤j≤1.5, 0≤k≤0.2.)
[0177] Examples of the alkali metal-containing transition metal phosphate compound include the following formula (4):
[0178] M e M 4 f (PO 4 ) g (4)
[0179] (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 4represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, 0.5≤e≤3, 1≤f≤2, 1≤g≤3). In the above, M is preferably a metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.
[0180] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples, LiFePO 4 , Li 3 Fe 2 (PO 4 ) 3 、LiFeP 2 O 7 Iron phosphates such as LiCoPO 4 Cobalt phosphates, etc.; substances obtained by replacing part of the transition metal atoms serving as the main body of these lithium transition metal phosphate compounds with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0181] The lithium-containing transition metal phosphate compound preferably has an olivine structure.
[0182] As other positive electrode active materials, MFePO can be cited. 4 、MNi 0.8 Co 0.2 O 2 、M 1.2 Fe 0.4 Mn 0.4 O 2 、MNi 0.5 Mn 1.5 O 2 , MV 3 O 6 、M 2 MnO 3 etc. In particular, M 2 MnO 3 、MNi 0.5 Mn 1.5 O 2 When the positive electrode active material is operated at a voltage exceeding 4.4V or a voltage above 4.6V, the crystal structure will not collapse, which is preferred from this aspect. Therefore, even if the electrochemical device such as the secondary battery using the positive electrode material including the positive electrode active material exemplified above is stored at high temperature, the residual capacity is not easy to decrease, the resistance increase rate is not easy to change, and even if it is operated at a high voltage, the battery performance will not deteriorate, so it is preferred.
[0183] As other positive electrode active materials, M can also be cited. 2 MnO 3 and MM 6 O 2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 is a transition metal such as Co, Ni, Mn, Fe, etc.) a solid solution material, etc.
[0184] As the above solid solution material, for example, it is a general formula M x [Mn (1-y) M 7 y O z shown alkali metal manganese oxide. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 is composed of at least one metal element other than M and Mn, and for example, contains one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. In addition, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O 2 Such a manganese-containing solid solution material based on Li 2 MnO 3 and solid-solved with LiNiO 2 , LiCoO 2 can provide an alkali metal ion secondary battery with high energy density and is preferred in this regard.
[0185] In addition, if the positive electrode active material contains lithium phosphate, the continuous charging characteristics are improved, so it is preferred. The use of lithium phosphate is not limited, and it is preferred to mix and use the above positive electrode active material with lithium phosphate. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, further preferably 0.5% by mass or more, based on the total lower limit of the above positive electrode active material and lithium phosphate, and the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, further preferably 5% by mass or less.
[0186] As the above sulfur-based material, materials containing sulfur atoms can be exemplified, preferably at least one selected from the group consisting of elemental sulfur, metal sulfides, and organic sulfur compounds, and more preferably elemental sulfur. The above metal sulfide can be a metal polysulfide. The above organic sulfur compound can be an organic polysulfide.
[0187] As the above metal sulfide, examples include: LiS x (0 < x ≤ 8); Li 2 S x (0 < x ≤ 8); TiS 2 , MoS 2 and other compounds with a two-dimensional layered structure; the general formula Me x Mo 6 S 8 (Me is various transition metals represented by Pb, Ag, Cu, 0 < x ≤ 8), Chevrel phase compounds with a firm three-dimensional framework structure, etc.
[0188] As the above organic sulfur compound, examples include carbon-sulfide ether compounds, etc.
[0189] The above organic sulfur compound is sometimes supported on a porous material such as carbon and used as a carbon composite material. Regarding the content of sulfur contained in the carbon composite material, for the reason of more excellent cycle performance and further reduced overvoltage, it is preferably 10% by mass to 99% by mass, more preferably 20% by mass or more, further preferably 30% by mass or more, particularly preferably 40% by mass or more, and preferably 85% by mass or less with respect to the above carbon composite material.
[0190] When the above positive electrode active material is the above sulfur element, the content of sulfur contained in the above positive electrode active material is equal to the content of the above sulfur.
[0191] As the conductive polymer, examples include p-doped conductive polymers and n-doped conductive polymers. As the conductive polymer, examples include polyacetylene-based, polystyrene-based, heterocyclic polymers, ionic polymers, ladder and network polymers, etc.
[0192] In addition, a substance having a different composition adhered to the surface of the above positive electrode active material can also be used. As the surface adhered substance, examples include oxides such as alumina, silica, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, magnesium carbonate; carbon; and so on.
[0193] These surface-attached substances can be attached to the surface of the positive electrode active material by, for example, the following methods: a method of dissolving or suspending the substance in a solvent and adding it to the positive electrode active material by infiltration and drying; a method of dissolving or suspending the surface-attached substance precursor in a solvent and adding it to the positive electrode active material by infiltration and then reacting it by heating or the like; a method of adding it to the positive electrode active material precursor and simultaneously firing it; etc. It should be noted that in the case of attaching carbon, a method of mechanically attaching carbon in the form of activated carbon or the like can also be used.
[0194] The amount of the surface-attached substance is used in the following amount relative to the mass of the positive electrode active material: preferably 0.1 ppm or more, more preferably 1 ppm or more, and further preferably 10 ppm or more as the lower limit, and preferably 20% or less, more preferably 10% or less, and further preferably 5% or less as the upper limit. The surface-attached substance can inhibit the oxidation reaction of the electrolyte on the surface of the positive electrode active material and improve the battery life, but if the amount of the attached substance is too small, the effect cannot be fully manifested; if it is too large, it will hinder the entry and exit of lithium ions, thereby possibly increasing the resistance.
[0195] The shape of the particles of the positive electrode active material may be block, polyhedron, sphere, ellipsoid, plate, needle, column, etc. The primary particles may be aggregated to form secondary particles.
[0196] The tap density of the positive electrode active material is preferably 0.5 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 1.0 g / cm 3 Above. If the tap density of the positive electrode active material is lower than the above lower limit, the amount of dispersion medium required when the positive electrode active material layer is formed increases, and the required amount of conductive material and binder increases, the filling rate of the positive electrode active material in the positive electrode active material layer is limited, and the battery capacity may be limited. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. The larger the tap density is, the better. There is no particular upper limit. However, if it is too large, the diffusion of lithium ions using the electrolyte in the positive electrode active material layer as a medium becomes rate-limiting, and sometimes the load characteristics are easily reduced. Therefore, the upper limit is preferably 4.0 g / cm 3 Below, more preferably 3.7 g / cm 3 Below, more preferably 3.5 g / cm 3 the following.
[0197] It should be noted that in the present disclosure, the tap density is the powder packing density (tap density) g / cm2 when 5 g to 10 g of the positive electrode active material powder is placed in a 10 ml glass measuring cylinder and vibrated 200 times with a stroke of about 20 mm. 3 Find out.
[0198] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter in the case where the primary particles are agglomerated to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, further preferably 0.8 μm or more, and most preferably 1.0 μm or more, and preferably 30 μm or less, more preferably 27 μm or less, further preferably 25 μm or less, and most preferably 22 μm or less. If it is less than the above lower limit, a high tap density product may not be obtained; if it exceeds the upper limit, the diffusion of lithium in the particles takes time, which sometimes leads to a decrease in battery performance, or when the positive electrode of the battery is made, that is, the active material and the conductive material, the binder, etc. are slurried with a solvent and coated into a thin film, causing problems such as stripes. Here, by mixing two or more of the above-mentioned positive electrode active materials with different median diameters d50, the filling property during the production of the positive electrode can be further improved.
[0199] It should be noted that in the present disclosure, the median diameter d50 is measured using a known laser diffraction / scattering particle size distribution measuring device. When using LA-920 manufactured by HORIBA as a particle size distribution meter, as a dispersion medium used during measurement, a 0.1% by mass sodium hexametaphosphate aqueous solution is used, and after 5 minutes of ultrasonic dispersion, the measured refractive index is set to 1.24 for measurement.
[0200] In the case where the primary particles are agglomerated to form secondary particles, the average primary particle size of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and further preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, further preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which has an adverse effect on the powder filling property, or the specific surface area is greatly reduced, so the possibility of reduced battery performance such as output characteristics is sometimes increased. On the contrary, if it is lower than the lower limit, crystallization is usually not developed, so problems such as poor reversibility of charge and discharge may occur.
[0201] It should be noted that in the present disclosure, the primary particle size is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph with a magnification of 10,000 times, for any 50 primary particles, the longest value of the slice intercepted on a straight line in the horizontal direction by the left and right boundaries of the primary particles is obtained, and the average value is taken to obtain the primary particle size.
[0202] The BET specific surface area of the positive electrode active material is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more, and the upper limit is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, and if it is larger than this range, it is difficult to increase the tap density, and coating properties may be problematic when the positive electrode active material layer is formed.
[0203] It should be noted that in the present disclosure, the BET specific surface area is defined as: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.), after pre-drying the sample at 150°C for 30 minutes under nitrogen flow, using a nitrogen-helium mixed gas accurately adjusted so that the relative pressure of nitrogen to atmospheric pressure becomes 0.3, the value is measured by the nitrogen adsorption BET single-point method based on the gas flow method.
[0204] When the secondary battery of the present disclosure is used as a large lithium ion secondary battery for hybrid vehicles or distributed power sources, high output is required, and therefore the particles of the positive electrode active material preferably mainly contain secondary particles.
[0205] The particles of the positive electrode active material preferably contain 0.5 volume % to 7.0 volume % of secondary particles with an average particle size of 40 μm or less and an average primary particle size of 1 μm or less. By containing particles with an average primary particle size of 1 μm or less, the contact area with the electrolyte becomes larger, which can make the diffusion of lithium ions between the electrode and the electrolyte faster, and as a result, the output performance of the battery can be improved.
[0206] As a method for producing the positive electrode active material, a common method for producing an inorganic compound is used. In particular, various methods are considered for producing a spherical or ellipsoidal active material, for example, the following method can be cited: dissolving or crushing a transition metal raw material in a solvent such as water, adjusting the pH under stirring, producing a spherical precursor and recovering it, drying it as needed, and then adding LiOH, Li 2 CO 3 、LiNO 3 The active material is obtained by sintering at high temperature with lithium source.
[0207] In order to manufacture the positive electrode, the above-mentioned positive electrode active materials may be used alone, or two or more of them with different compositions may be used together in any combination or ratio. As a preferred combination in this case, LiCoO 2 With LiNi0.33 Co 0.33 Mn 0.33 O 2 LiMn 2 O 4 or a combination of replacing part of the Mn with other transition metals, or LiCoO 2 Alternatively, a part of the Co may be replaced with other transition metals or the like.
[0208] From the viewpoint of increasing the battery capacity, the content of the positive electrode active material is preferably 50% by mass to 99.5% by mass of the positive electrode mixture, and more preferably 80% by mass to 99% by mass.
[0209] In addition, the content of the positive electrode active material in the positive electrode active material layer is preferably 80 mass % or more, more preferably 82 mass % or more, and particularly preferably 84 mass % or more. In addition, the upper limit is preferably 99 mass % or less, more preferably 98 mass % or less. When the content of the positive electrode active material in the positive electrode active material layer is low, the capacitance sometimes becomes insufficient. On the contrary, when the content is too high, the strength of the positive electrode is sometimes insufficient.
[0210] The positive electrode active material layer preferably further includes a binder, a thickener, and a conductive material.
[0211] As the above-mentioned binder, any substance can be used as long as it is a material safe for the solvent and electrolyte used in electrode manufacturing, and examples thereof include: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, chitosan, alginic acid, polyacrylic acid, polyimide, cellulose, and nitrocellulose; rubber polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers. or its hydrogenated product; thermoplastic elastomer polymers such as EPDM (ethylene propylene diene terpolymer), styrene ethylene butadiene styrene copolymer, styrene isoprene styrene block copolymer or its hydrogenated product; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene vinyl acetate copolymer, propylene α-olefin copolymer; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride copolymer, tetrafluoroethylene ethylene copolymer; polymer compositions having ion conductivity of alkali metal ions (particularly lithium ions), etc. These may be used alone or in any combination and ratio.
[0212] The content of binder is usually 0.1 mass % or more, preferably 1 mass % or more, more preferably 1.5 mass % or more, and usually 80 mass % or less, preferably 60 mass % or less, more preferably 40 mass % or less, most preferably 10 mass % or less. If the ratio of binder is too low, positive electrode active material cannot be fully maintained, and the mechanical strength of positive electrode is sometimes insufficient, and battery performance such as cycle characteristics is sometimes deteriorated. On the other hand, if the ratio of binder is too high, it sometimes leads to a reduction in battery capacity and conductivity.
[0213] Examples of the thickener include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, polyvinyl pyrrolidone, and salts thereof. One type may be used alone, or two or more types may be used in any combination and ratio.
[0214] The ratio of thickener to active material is usually 0.1 mass %, preferably 0.2 mass %, more preferably 0.3 mass %, and usually 5 mass %, preferably 3 mass %, more preferably 2 mass %. If it is lower than this scope, the coating property is significantly reduced sometimes. If it is higher than this scope, the proportion of active material in positive electrode active material layer is reduced, and sometimes the problem of reduced capacity of battery or the problem of increased resistance between positive electrode active materials is generated.
[0215] As the above-mentioned conductive material, any known conductive material can be used. As specific examples, metal materials such as copper and nickel, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, needle coke, carbon nanotubes, fullerene, carbon materials such as amorphous carbon such as VGCF, etc. can be cited. It should be noted that these can be used alone or in any combination and ratio. Two or more kinds can be used together.
[0216] The conductive material is usually 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 1% by mass or more in the positive electrode active material layer, and is usually used in a manner containing 50% by mass or less, preferably 30% by mass or less, and more preferably 15% by mass or less. If the content is lower than this range, the conductivity is sometimes insufficient. On the contrary, if the content is higher than this range, the battery capacity is sometimes reduced.
[0217] As a solvent for forming the slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the binder, and the thickener used as needed, its type is not particularly limited, and any of aqueous solvents and organic solvents can be used. As aqueous solvents, for example, water, mixed solvents of alcohol and water, etc. can be cited. As organic solvents, for example, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; non-protonic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0218] The amount of the solvent to be blended is determined in consideration of coating properties on a current collector, thin film forming properties after drying, etc. The ratio of the binder to the solvent is preferably 0.5:99.5 to 20:80 by weight.
[0219] Examples of the material of the positive electrode current collector include metals such as aluminum, titanium, tantalum, stainless steel, nickel, or alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or alloys thereof, are preferred.
[0220] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal film, porous metal mesh, stamping metal, foamed metal, etc. can be mentioned, and in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be mentioned. Among these, metal film is preferred. It should be noted that the film can be appropriately formed into a mesh. The thickness of the film is arbitrary, usually more than 1 μm, preferably more than 3 μm, more preferably more than 5 μm, and usually less than 1 mm, preferably less than 100 μm, more preferably less than 50 μm. If the film is thinner than this range, the strength required as a current collector is sometimes insufficient. On the contrary, if the film is thicker than this range, sometimes the handling property is impaired.
[0221] In addition, from the perspective of reducing the electrical contact resistance between the current collector and the positive electrode active material layer, it is also preferred that a conductive additive be coated on the surface of the current collector. Examples of the conductive additive include carbon or noble metals such as gold, platinum, and silver.
[0222] The ratio of the thickness of the current collector to the positive electrode active material layer is not particularly limited, and the value of (the thickness of the positive electrode active material layer on one side before the electrolyte is injected) / (the thickness of the current collector) is preferably less than 20, more preferably less than 15, and most preferably less than 10. In addition, it is preferably more than 0.5, more preferably more than 0.8, and most preferably more than 1. If it is higher than this range, the current collector sometimes generates heat caused by Joule heat during high current density charging and discharging. If it is lower than this range, the volume ratio of the current collector to the positive electrode active material increases, and the capacity of the battery sometimes decreases.
[0223] The positive electrode can be manufactured according to conventional methods. For example, a method can be cited in which a slurry-like positive electrode mixture is prepared by adding the above-mentioned binder, thickener, conductive material, solvent, etc. to the above-mentioned positive electrode active material, applying the slurry to the collector, and pressing it after drying to obtain a high density.
[0224] The density increase can be achieved by hand pressing, roll pressing, etc. The density of the positive electrode active material layer is preferably 1.5 g / cm 3 More preferably, 2 g / cm 3 More preferably, 2.2 g / cm 3 More than 5 g / cm 3 Below, more preferably 4.5g / cm 3 Below, more preferably 4g / cm 3 If the value is higher than this range, the permeability of the electrolyte to the collector / active material interface decreases, and the charge-discharge characteristics under high current density decrease, and sometimes high output cannot be obtained. In addition, if the value is lower than this range, the conductivity between active materials decreases, and sometimes the battery resistance increases and high output cannot be obtained.
[0225] The thickness of the positive electrode plate is not particularly limited. From the perspective of high capacity and high output, the thickness of the positive electrode active material layer after deducting the thickness of the metal foil of the core material is preferably 10 μm or more, more preferably 20 μm or more, and preferably 500 μm or less, more preferably 450 μm or less, relative to a single side of the collector as the lower limit.
[0226] In addition, a positive electrode plate having a substance having a different composition attached to the surface of the positive electrode plate may also be used. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; carbon; and the like.
[0227] <Diaphragm>
[0228] The secondary battery of the present disclosure preferably further includes a separator.
[0229] The material and shape of the separator are not particularly limited as long as the electrolyte is stable and the liquid retention is excellent, and a known separator can be used. Preferably, a porous sheet or nonwoven fabric-like material with excellent liquid retention, such as resin, glass fiber, or inorganic material, is used.
[0230] As materials for the resin and glass fiber separator, for example, polyolefins such as polyethylene and polypropylene, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, glass filters, etc. can be used. Polypropylene / polyethylene two-layer membranes, polypropylene / polyethylene / polypropylene three-layer membranes, etc. These materials can be used alone or in any combination and ratio.
[0231] Among them, the separator is preferably a porous sheet or nonwoven fabric made of polyolefin such as polyethylene or polypropylene from the viewpoint of good electrolyte permeability and shutdown effect.
[0232] The thickness of the separator is arbitrary, usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is too thin compared to the above range, the insulation and mechanical strength may sometimes be reduced. In addition, if it is too thick compared to the above range, the battery performance such as rate characteristics may sometimes be reduced, and the energy density of the electrolyte battery as a whole may sometimes be reduced.
[0233] In addition, when a porous material such as a porous sheet or nonwoven fabric is used as a diaphragm, the porosity of the diaphragm is arbitrary, usually 20% or more, preferably 35% or more, more preferably 45% or more, and usually 90% or less, preferably 85% or less, more preferably 75% or less. If the porosity is too small compared to the above range, there is a tendency for the membrane resistance to increase and the rate characteristics to deteriorate. In addition, if it is too large compared to the above range, there is a tendency for the mechanical strength of the diaphragm to decrease and the insulation to decrease.
[0234] In addition, the average pore size of the diaphragm is also arbitrary, usually 0.5 μm or less, preferably 0.2 μm or less, and usually 0.05 μm or more. If the average pore size exceeds the above range, short circuit is likely to occur. In addition, if it is less than the above range, the membrane resistance sometimes increases and the rate characteristics decrease.
[0235] On the other hand, as inorganic materials, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate are used, and materials in the form of particles or fibers are used.
[0236] As a form, a non-woven fabric, a woven fabric, a microporous film or other thin film-shaped material is used. In the case of a thin film, a film with a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm is preferably used. In addition to the above-mentioned independent thin film shape, a separator formed by forming a composite porous layer containing particles of the above-mentioned inorganic substance on the surface of the positive electrode and / or the negative electrode using a resin binder can also be used.
[0237] For example, a fluororesin is used as a binder, and alumina particles having a particle size of 90% less than 1 μm are formed into a porous layer on both sides of the positive electrode.
[0238] <Electrolyte>
[0239] In the secondary battery of the present disclosure, a non-aqueous electrolyte is preferably used as the electrolyte. As the non-aqueous electrolyte, a non-aqueous electrolyte obtained by dissolving a known electrolyte salt in a known organic solvent for dissolving the electrolyte salt can be used.
[0240] There is no particular limitation on the organic solvent used to dissolve the electrolyte salt, and known hydrocarbon solvents such as propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and propyl propionate (PrPr) can be used; and one or more of fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.
[0241] Examples of the electrolyte salt include LiClO 4 、LiAsF 6 , LiBF 4 、LiPF 6 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 In terms of good cycle characteristics, LiPF is particularly preferred. 6 , LiBF 4 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 or a combination thereof.
[0242] The concentration of the electrolyte salt needs to be 0.8 mol / L or more, and further needs to be 1.0 mol / L or more. The upper limit also depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L.
[0243] In addition, a gel electrolyte may be used in the secondary battery of the present disclosure. The gel electrolyte is not particularly limited, and any material such as an electrolyte, a solvent, and a gel matrix contained in a conventional composition for forming a gel electrolyte layer may be used.
[0244] As the electrolyte, for example, the electrolytes exemplified above can be cited. Specifically, Li(CF 3 SO 2 ) 2 N、Li(C 2 F 5 SO 2 ) 2 N、LiPF 6 , LiBF 4 、LiAsF 6 、LiTaF 6 、LiClO 4 、LiCF 3 SO 3 And other lithium salts.
[0245] Examples of the solvent include the carbonate-based organic solvents described above.
[0246] Examples of the gel matrix (matrix polymer) include polyethylene oxide (PEO), polypropylene oxide (PPO), PVDF, PVDF-HFP, polyethylene glycol (PEG), polyacrylonitrile (PAN), and polymethyl methacrylate (PMMA).
[0247] <Battery Design>
[0248] A secondary battery using the battery casing disclosed in the present invention is particularly preferably a thin battery such as a laminated battery. Regarding the appearance of the laminated battery, the battery constituent materials are stored in the battery shell so that a portion of the electrode terminal protrudes to the outside of the above-mentioned battery. As a state in which the battery constituent materials are stored, the battery casing includes an electromotive unit and a portion of the electrode terminal extending from the unit, and the portion between the electrode terminal protruding to the outside of the battery casing and the electrode terminal in the battery casing is tightly bonded at the heat-sealing portion when the battery casing is formed to form a sealed state. The electrode terminal protrudes to the outside of the casing, so in order to reliably seal the battery casing as an outer casing, a portion of the electrode terminal is thermally bonded to the heat-sealing resin at the heat-sealing portion of the outer casing.
[0249] By using the fluororesin film of the present disclosure as the innermost heat-sealed portion, the heat-sealed portions themselves have thermal adhesiveness, and the electrode terminals formed of conductive materials such as copper foil and aluminum foil, which are the forming materials of the electrode terminals, also have good thermal adhesiveness.
[0250] The present disclosure also relates to a secondary battery, wherein the fluororesin film of the battery exterior body is present at a position in contact with an electrolyte solution.
[0251] The fluororesin film of the present disclosure is stable to electrolyte, and therefore, in a secondary battery, the fluororesin film of the present disclosure is used as the innermost layer of the battery exterior body and the fluororesin film of the present disclosure is brought into contact with the electrolyte, thereby making it possible to produce a secondary battery that further exhibits the effect of resistance to electrolyte permeation.
[0252] The manufacturing method of the laminated battery is not particularly limited, and the following method can be cited as an example. In the element of a large laminated lithium-ion battery, an element in which a positive electrode, a negative electrode, and a separator are combined in a stacked manner is produced. Usually, an element composed of 20 to 40 positive electrodes and negative electrodes is combined into one element.
[0253] Next, the tabs are mounted on the above-mentioned element. The tabs may come out from both ends or from the same side.
[0254] Then, the sheet-like outer package is clamped from both sides of the element and sealed. At this time, in order to inject the electrolyte, the opening can be opened without sealing one side, and the electrolyte can be injected from there, or the shape of the laminated material can be made into a shape that is easy to inject liquid (pre-set the injection port, etc.), and the liquid can be injected from there.
[0255] Next, the liquid injection portion is also sealed to obtain a laminated battery.
[0256] Example
[0257] The present disclosure will be specifically described below based on examples. However, the present invention is not limited to the following examples.
[0258] (Polymer composition)
[0259] The determination was carried out by 19F-NMR analysis.
[0260] (Melting Point)
[0261] The molecular weight was calculated from the melting peak when the temperature was increased at a rate of 10° C. / min using a DSC apparatus.
[0262] (Glass transition temperature)
[0263] The tan δ value was calculated from the tan δ peak when the measurement was performed using a solid dynamic viscoelasticity apparatus (DMA) at a frequency of 10 Hz, a strain of 0.1%, and a heating rate of 5° C. / min.
[0264] (Melt flow rate (MFR)
[0265] The measurement was performed in accordance with ASTM D3307 at a temperature of 372° C. and a load of 5.0 kg.
[0266] (Thickness of fluororesin film)
[0267] The measurement was performed using a micrometer.
[0268] (Ratio of oxygen element on the surface of fluororesin film)
[0269] After the sample film was heat treated at 180°C for 3 minutes, the surface state of one or both sides was measured using a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) PHI5000VersaProbeII (manufactured by ULVAC-PHI Co., Ltd.) with an X-ray source: monochromatized AlKα rays and an incident angle of 45°, and the proportion of oxygen element in fluorine, carbon, oxygen, and nitrogen was calculated.
[0270] In order to determine the oxygen element ratio difference in the depth direction described below, the oxygen element ratio on the surface of the fluororesin film was calculated without performing a heat treatment at 180° C. for 3 minutes.
[0271] (Difference in oxygen ratio in the depth direction)
[0272] The sample film was etched in the depth direction for 15 minutes using an argon cluster ion beam at an incident angle of 45° and sputtering conditions of 2.5 kV×10 nA. The film was then analyzed under the conditions described above, and the oxygen element ratio was calculated to obtain the difference from the oxygen element ratio on the surface of the fluororesin film described above.
[0273] (Dimensional change rate)
[0274] Marking points were set at intervals of 180 mm in the MD and TD directions of a film sample cut into 300 mm square, and the sample was placed on a metal plate covered with PTFE-impregnated glass cloth. After heat treatment for 10 minutes in an electric furnace set at an air atmosphere of 180°C without applying a load, a vernier caliper (in mm, measurable to the second decimal place) was used to measure the marking point intervals in the MD and TD directions of the film cooled to 25°C (standing in a room at 25°C for more than 30 minutes), and the change in the marking point intervals before and after the heat treatment was calculated using the following formula.
[0275] Thermal shrinkage = {(length after heat treatment - length before heat treatment) / length before heat treatment} × 100 (%)
[0276] (Wrinkles after annealing)
[0277] Visually check for wrinkles
[0278] ○···No deformation (undulation) of the film occurs
[0279] ×…Produces film deformation (undulation)
[0280] (Wrinkles of film roll)
[0281] The appearance of the rolled product was visually evaluated after being stored at room temperature for 1 month.
[0282] 〇…No wrinkles are generated or increased due to tight winding
[0283] ×…Wrinkles are generated / increased due to tight winding
[0284] (Adhesion strength between fluororesin films)
[0285] The surface treated surfaces of the fluororesin films were overlapped, and a sample produced by hot pressing (200°C, 0.2 MPa, 120 s) was cut into strips 10 mm wide. The peel strength was measured by using a Tensilon universal testing machine (manufactured by Shimadzu Corporation) while clamping the unbonded portion of the strip sample between the upper and lower chucks of the Tensilon and stretching it at a speed of 100 mm per minute. The obtained value was used as the bonding strength.
[0286] (Electrolyte Permeability of Fluororesin Membrane)
[0287] The membrane (resin membrane layer) for evaluating permeability was cut into pieces of Φ6 cm. Figure 1 As shown, sandwiched between two glassware ( Figure 1 3 indicates the film to be evaluated). One chamber 2 of the glassware was filled with 200 mL of 2-propanol, and the other chamber 4 was filled with 200 mL of an electrolyte solution to which LiPF was added in a concentration of 1.2 mol / L in a solution composed of ethylene carbonate, fluoroethylene carbonate, and dimethyl carbonate in a volume ratio of 20 / 10 / 70. 6 The two chambers were sealed by plugging. The entire glassware was immersed in a 60°C warm bath 1, and 2-propanol was collected after 30 days. The electrolyte that permeated the resin membrane layer was quantified by gas chromatography. 2 ) was used to calculate the electrolyte permeability.
[0288] (Bond strength with aluminum foil)
[0289] The surface-treated surface of the film was brought into contact with aluminum foil 8079 material (manufactured by Toyo Aluminum Co., Ltd., film thickness 40 μm), and the films were overlapped in the order of aluminum foil / film / aluminum foil. A vacuum hot press (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) was used to perform hot pressing at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds to achieve bonding. An aluminum plate was attached to one side of the laminate made by vacuum hot pressing using tape. A Tensilon universal testing machine (manufactured by Shimadzu Corporation) was used to grasp a 10 mm wide aluminum foil in a direction of 90° relative to the plane of the laminate at a speed of 50 mm per minute and stretch it. The peel strength of the aluminum foil was measured, and the resulting value was used as the bonding strength.
[0290] (Sample 1)
[0291] As a fluororesin, PFA (TFE / PPVE copolymer, composition: TFE / PPVE=98.4 / 1.6 (mol%), MFR: 15.8 g / 10 min, melting point: 305°C) was melt-extruded by a T-die method and wound up to obtain a long roll film with a thickness of 50 μm. Both sides of the roll film were surface-treated (nitrogen containing 0.50% by volume of vinyl acetate was circulated near the discharge electrode and the roll-shaped ground electrode of the corona discharge device, and the film was continuously passed along the roll-shaped ground electrode at a discharge amount of 1324 W·min / m 2 Both surfaces of the film were subjected to corona discharge treatment, and the surface-treated long film was rolled up. The surface oxygen ratio of the surface-treated film according to ESCA surface analysis was 20.42 atomic %. In addition, the glass transition temperature of the film was 92°C.
[0292] (Sample 2)
[0293] FEP (TFE / HFP copolymer: composition: TFE / HFP=93.2 / 6.8 (mol%), MFR7.5 (g / 10 min), melting point 270 (°C)) produced by the manufacturing method of Comparative Example 5 of Japanese Patent Publication No. 57-040847 was melt-extruded and rolled up to obtain a long roll film with a thickness of 50 μm. Both sides of the long roll film were surface treated (nitrogen containing 0.50 volume % of vinyl acetate was circulated near the discharge electrode and the rolled ground electrode of the corona discharge device, and the film was continuously passed along the rolled ground electrode at a discharge amount of 1324 W·min / m 2 Both surfaces of the film were subjected to corona discharge treatment, and the surface-treated long film was rolled up. The surface oxygen element ratio of the surface-treated film according to ESCA surface analysis was 19.87 atomic %. In addition, the glass transition temperature of the film was 81°C.
[0294] (Sample 3)
[0295] In addition to making the discharge capacity 265W·min / m 2 A sample in which both surfaces of a 50 μm-thick film were surface-treated was obtained in the same manner as in Sample 2. The surface oxygen element ratio of the surface-treated film according to ESCA surface analysis was 10.21 atomic %.
[0296] (Sample 4)
[0297] In addition to making the discharge capacity 132W·min / m 2 A sample in which both surfaces of a 50 μm-thick film were surface-treated was obtained in the same manner as in Sample 2. The surface oxygen element ratio of the surface-treated film according to ESCA surface analysis was 4.33 atomic %.
[0298] (Sample 5)
[0299] In addition to making the discharge capacity 66W·min / m 2 A sample in which both surfaces of a 50 μm-thick film were surface-treated was obtained in the same manner as in Sample 2. The surface oxygen element ratio of the surface-treated film according to ESCA surface analysis was 2.61 atomic %.
[0300] (Sample 6)
[0301] A commercially available unstretched polypropylene film for a heat-sealing layer (CT P1146 manufactured by Toyobo Co., Ltd., film thickness 50 μm) was purchased.
[0302] Table 1 shows the results of the above samples 1 to 6.
[0303] [Table 1]
[0304]
[0305] (Example 1)
[0306] The electrolyte permeability of the resin membrane was evaluated using the membrane of sample 1, and the result was 18 g / m 2 ·day.
[0307] (Example 2)
[0308] The electrolyte permeability of the resin membrane was evaluated using the membrane of sample 2, and the result was 7 g / m 2 ·day.
[0309] (Comparative Example 1)
[0310] The electrolyte permeability of the resin membrane was evaluated using the membrane of sample 6. The result was 2597 g / m 2·day.
[0311] Table 2 shows the results of Examples 1 and 2 and Comparative Example 1.
[0312] [Table 2]
[0313] Example 1 Example 2 Comparative Example 1 Use resin film Sample 1 Sample 2 Sample 6 <![CDATA[Electrolyte permeability of the resin film (g / m 2 ·day)]]> 18 7 2597
[0314] The above results show that the fluororesin film is superior to the unstretched polypropylene film used as the heat-sealed layer of the conventional battery outer casing in terms of resistance to electrolyte permeation. It is also known that FEP is superior to PFA in terms of resistance to electrolyte permeation.
[0315] (Example 3)
[0316] The film of sample 1 is passed through an annealing furnace at 180°C (under air atmosphere) in a roll-to-roll manner, the film is cooled in the cooling area, and the long film is rolled into a roll. At this time, the deformation (undulation) of the annealed film is visually evaluated. Next, the cut film sampled from the long roll film is placed in an electric furnace at 180°C for 10 minutes for heat treatment and then cooled to room temperature. Then, the dimensional change rate in the MD / TD direction is measured and its absolute value is obtained. In addition, the film rolled on the core is stored at room temperature for 1 month, and the winding tightness is evaluated.
[0317] (Example 4)
[0318] Annealing treatment and subsequent evaluation of the presence or absence of deformation (undulation) of the film, measurement of the dimensional change rate, and evaluation of winding tightness were performed in the same manner as in Example 3 except that the film of Sample 2 was used.
[0319] (Example 5)
[0320] Annealing treatment and subsequent evaluation of film deformation (undulation), measurement of dimensional change rate, and evaluation of winding tightness were performed in the same manner as in Example 4 except that the temperature of the annealing furnace was set at 200°C.
[0321] (Example 6)
[0322] Annealing treatment and subsequent evaluation of the presence or absence of deformation (undulation) of the film, measurement of the dimensional change rate, and evaluation of winding tightness were performed in the same manner as in Example 3 except that the film of Sample 3 was used.
[0323] (Example 7)
[0324] Annealing treatment and subsequent evaluation of the presence or absence of deformation (undulation) of the film, measurement of the dimensional change rate, and evaluation of winding tightness were performed in the same manner as in Example 3 except that the film of Sample 4 was used.
[0325] (Example 8)
[0326] Annealing treatment and subsequent evaluation of the presence or absence of deformation (undulation) of the film, measurement of the dimensional change rate, and evaluation of winding tightness were performed in the same manner as in Example 4 except that the film of Sample 5 was used.
[0327] (Example 9)
[0328] Annealing treatment and subsequent evaluation of film deformation (undulation), measurement of dimensional change rate, and evaluation of winding tightness were performed in the same manner as in Example 4 except that a cooling zone was not included in the annealing step.
[0329] (Comparative Example 2)
[0330] Annealing treatment and subsequent evaluation of film deformation (undulation), measurement of dimensional change rate, and evaluation of winding tightness were performed in the same manner as in Example 4 except that the temperature of the annealing furnace was set at 250°C.
[0331] (Comparative Example 3)
[0332] The dimensional change rate of Sample 2 which was not subjected to annealing treatment was measured and the winding tightness was evaluated.
[0333] Table 3 shows the results of Examples 3 to 9 and Comparative Examples 2 to 3.
[0334] [Table 3]
[0335]
[0336] According to the results in Table 3, by adjusting the annealing conditions so that the absolute value of the dimensional change rate after the heat treatment at 180°C × 10 minutes is less than 2%, the winding tightness caused by the change over time can be suppressed. In addition, in the case where the cooling zone is not added to the annealing process in Comparative Example 2, deformation (undulation) occurs when the annealed roll film is unwound, and the winding tightness cannot be evaluated. In this state, defects occur in the process of laminating with aluminum foil, etc., so it is preferable to add a cooling process to the annealing process.
[0337] (Example 10)
[0338] The film annealed in Example 3 (Sample 1: 180) was cut into 100 mm squares, placed on a metal tray, and heat treated in an electric furnace (air atmosphere) at 180° C. for 3 minutes. The surface of the film in contact with air during the heat treatment was analyzed by ESCA.
[0339] Next, the surface on which the heat-treated fluororesin film was subjected to surface analysis was overlapped with aluminum foil 8079 material (manufactured by Toyo Aluminum Co., Ltd., film thickness 40 μm) in contact, and hot pressing was performed using a vacuum hot press machine (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds to achieve bonding, and the bonding strength was measured by peeling at 90° using a Tensilon universal testing machine.
[0340] (Example 11)
[0341] Surface analysis by ESCA and measurement of adhesive strength were performed in the same manner as in Example 10, except that the film (Sample 2: 180) subjected to the annealing treatment in Example 4 was used.
[0342] (Example 12)
[0343] The surface of the film (sample 3: 180) subjected to annealing treatment in Example 6 was analyzed by ESCA, and the result showed that the oxygen element ratio was 8.12 atomic%. In addition, after etching in the depth direction for 15 minutes using an argon cluster ion beam at an incident angle of 45° and sputtering conditions of 2.5 kV×10 nA, the surface was analyzed by ESCA, and the result showed that the oxygen element ratio was 0.91 atomic%. The difference between the two results was 7.21 atomic%. In addition, the bonding strength between the annealed film and the aluminum foil was 968 N / m, and the bonding strength between the treated surfaces of the film was 237 N / m.
[0344] Next, the film (Sample 3: 180) annealed in Example 6 was cut into 100 mm squares, placed on a metal tray, and placed in an electric furnace (air atmosphere) at 180° C. for 3 minutes for heat treatment. The surface of the film that was in contact with air during the heat treatment was analyzed by ESCA.
[0345] Next, the surface on which the heat-treated fluororesin film was subjected to surface analysis was overlapped with aluminum foil 8079 material (manufactured by Toyo Aluminum Co., Ltd., film thickness 40 μm) in contact, and hot pressing was performed using a vacuum hot press machine (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a pressing temperature of 320°C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds to achieve bonding, and the bonding strength was measured by peeling at 90° using a Tensilon universal testing machine.
[0346] (Example 13)
[0347] Surface analysis by ESCA and measurement of adhesive strength were performed in the same manner as in Example 10, except that the film (Sample 4: 180) subjected to the annealing treatment in Example 7 was used.
[0348] (Comparative Example 4)
[0349] The film of sample 5 was passed through an annealing furnace at 180°C (under air atmosphere) in a roll-to-roll manner, and the film was cooled in a cooling zone, and the long film was rolled into a roll. The oxygen element ratio on the surface of the film after annealing was 1.69%. In addition, after etching in the depth direction for 15 minutes using an argon cluster ion beam at an incident angle of 45° and sputtering conditions of 2.5kV×10nA, the surface was analyzed by ESCA, and the result showed that the oxygen element ratio was 0.84 atomic%. The difference between the two results was 0.85 atomic%.
[0350] Next, heat treatment at 180°C for 3 minutes, surface analysis, and measurement of bonding strength to aluminum foil were performed in the same manner as in Example 11. The oxygen element ratio on the film surface after the heat treatment was 1.28%, and the bonding strength to the aluminum foil was 650 N / mm.
[0351] (Comparative Example 5)
[0352] For both sides of a film with a thickness of 50 μm, which was melt-extruded by the T-die method in the same manner as sample 2, a discharge treatment without using an inert gas containing an organic compound was performed for surface treatment. The film was passed through an annealing furnace at 180°C (under an air atmosphere) in a roll-to-roll manner, and the film was cooled in a cooling zone and wound into a roll. The oxygen element ratio on the surface of the film after annealing was 4.01%. In addition, the bonding strength between the treated surfaces of the film was 26 N / m. Then, a heat treatment of 180°C × 3 minutes, surface analysis, and bonding strength with aluminum foil were performed in the same manner as in Example 11. The oxygen element ratio on the surface of the film after heat treatment was 0.88%, and the bonding strength with aluminum foil was 142 N / mm.
[0353] Table 4 shows the results of Examples 10 to 13 and Comparative Examples 4 and 5.
[0354] [Table 4]
[0355]
[0356] According to the results in Table 4, by making the oxygen element ratio of the film surface after heat treatment at 180°C for 3 minutes to be 1.35 atomic % or more, it is possible to obtain a bonding strength of 500 N / m or more with the aluminum foil. In particular, in the case of the surface treatment using an inert gas containing an organic compound disclosed in the present invention, there is less deactivation due to heat, and it can be used appropriately. It can be seen from this that the fluororesin film in the present invention can obtain sufficient bonding strength even if it is preheated in advance and then bonded to the aluminum foil in the lamination process, etc.
[0357] (Example 14)
[0358] The surface treated surface of the film (Sample 1: 180) subjected to annealing treatment in Example 3 was overlapped with aluminum foil 8079 material (manufactured by Toyo Aluminum Co., Ltd., film thickness 40 μm) in a contacting manner, and heat-pressed using a vacuum heat press (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a pressing temperature of 320° C., a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds to bond them together to produce a laminate. Two 10 cm×10 cm square-shaped laminates were cut out from the laminate, and the three overlapping sides were heat-sealed using an impulse heat sealer at 270° C., a pressure of 0.2 MPa, a pressing time of 120 seconds, and a sealing width of 5 mm in a state where the resin layers were facing each other. 5 mL of an electrolyte solution was added from the unsealed side of the obtained bag-like structure. The electrolyte solution was prepared by adding LiPF to a solution composed of ethylene carbonate, fluoroethylene carbonate, and dimethyl carbonate in a volume ratio of 20 / 10 / 70 to give a concentration of 1.2 mol / L. 6 The unsealed side was sealed with a clip. The side opposite to the unsealed side was placed downward and immersed in a 2-propanol bath at a distance of 1 cm from the bottom of the bag-like structure for 90 days. The amount of electrolyte dissolved in 2-propanol was quantified by gas chromatography, and the electrolyte permeability from the heat-sealed part was calculated as the permeation amount (g) per month (30 days).
[0359] (Example 15)
[0360] The electrolyte permeability from the heat-sealed portion was evaluated in the same manner as in Example 14, except that the film subjected to the annealing treatment in Example 4 (Sample 2: 180) was used.
[0361] (Comparative Example 6)
[0362] Using a commercially available aluminum laminate film for batteries (D-EL40H manufactured by Dai Nippon Printing Co., Ltd.) using a polypropylene film as a heat-sealing layer, two 10 cm × 10 cm square-shaped laminates were cut out from the laminate, and the three overlapping sides were heat-sealed using an impulse heat sealer (FCB-200 manufactured by FUJI IMPULSE Co., Ltd.) at 200°C, a pressing time of 3 seconds, and a sealing width of 5 mm with the heat-sealed layers facing each other. Except for this, the electrolyte permeability from the heat-sealed portion was evaluated in the same manner as in Example 12.
[0363] The results of Examples 14 and 15 and Comparative Example 6 are shown in Table 5.
[0364] [Table 5]
[0365] Embodiment 14 Embodiment 15 Comparative Example 6 Electrolyte permeability of resin membrane (g / month) 1.22 0.75 3.76
[0366] According to Table 5, the laminate using the fluororesin film as the heat seal layer can effectively suppress the permeation of the electrolyte from the heat seal portion. This is considered to be because, as can be seen from the results of Examples 1, 2, and Comparative Example 1 (Tables 2 and 3), the electrolyte permeability of the fluororesin in direct contact with the electrolyte is low.
[0367] (Production of battery outer casing)
[0368] (Example 16)
[0369] The surface treated surface of the film (Sample 2: 180) subjected to annealing treatment in Example 4 was overlapped in contact with aluminum foil 8079 material (manufactured by Toyo Aluminum Co., Ltd., film thickness 40 μm), and hot pressed using a vacuum hot press machine (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a pressing temperature of 320° C., a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds to bond them together to produce a laminate. A piece with a width of 125 mm and a length of 140 mm was cut from the laminate to form a battery outer package.
[0370] (Example 17)
[0371] The surface treated surface of an unstretched polypropylene film (CT P1146 manufactured by Toyobo Co., Ltd., film thickness 50 μm) was overlapped in such a way that the aluminum exposed surface of the laminate prepared in the same manner as in Example 16 was in contact, and heat-pressed using a vacuum hot press (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a pressing temperature of 180° C., a preheating time of 30 seconds, a pressure of 1.5 MPa, and a pressing time of 300 seconds to bond them together to prepare a laminate consisting of three layers of polypropylene film / aluminum foil / FEP film. A piece with a width of 125 mm and a length of 140 mm was cut from the laminate to form a battery outer package.
[0372] (Example 18)
[0373] Aluminum foil 8079 material (manufactured by Toyo Aluminum Co., Ltd., film thickness 40 μm), the film annealed in Example 4 (sample 2: 180), a polyimide film (manufactured by DuPont Toray Co., Ltd. 100H, film thickness 25 μm) dried at 120° C. for 12 hours, and the film annealed in Example 4 (sample 2: 180) were sequentially stacked and bonded by heat pressing using a vacuum hot press (model: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a pressing temperature of 275° C., a preheating time of 180 seconds, a pressure of 1.5 MPa, and a pressing time of 420 seconds to produce a laminate. A piece with a width of 125 mm and a length of 140 mm was cut out from the laminate to form a battery outer package.
[0374] (Manufacturing of lithium-ion secondary batteries)
[0375] [Preparation of electrolyte]
[0376] Ethylene carbonate and fluoroethylene carbonate as high dielectric constant solvents and dimethyl carbonate as low viscosity solvent were mixed at a volume ratio of 20 / 10 / 70, and LiPF was added thereto at a concentration of 1.2 mol / L. 6 , and obtain a non-aqueous electrolyte.
[0377] [Production of positive electrode]
[0378] LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O 2 95 mass % of (NMC), 2 mass % of acetylene black as a conductive material, and 3 mass % of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methylpyrrolidone solvent and slurried. On a 15 μm thick aluminum foil collector, the obtained slurry was applied to one side of the 15 μm thick aluminum foil, dried, and rolled using a press. The pressed product was cut into a shape with a width of 50 mm and a length of 30 mm and a width of 5 mm and a length of 9 mm uncoated portion according to the size of the active material layer, as a positive electrode.
[0379] [Production of negative electrode]
[0380] 1 mass part of an aqueous dispersion of sodium carboxymethylcellulose (1 mass% concentration of sodium carboxymethylcellulose) as a thickener and a binder and 1 mass part of an aqueous dispersion of styrene-butadiene rubber (50 mass% concentration of styrene-butadiene rubber) were added to 98 mass parts of carbonaceous material (graphite), and the mixture was mixed and slurried using a disperser. The obtained slurry was applied to a copper foil having a thickness of 10 μm and dried, and rolled using a press, and the rolled product was cut into a shape having a width of 52 mm, a length of 32 mm, and a width of 5 mm, and a length of 9 mm uncoated portion according to the size of the active material layer, as a negative electrode.
[0381] (Example 19)
[0382] [Manufacturing of aluminum laminated batteries]
[0383] The battery outer body obtained in Example 16 was folded in half along the length direction with the fluororesin film layer as the inner side, and a microporous polyethylene film (diaphragm, width 45mm, length 77mm) with a thickness of 20μm was placed inside so that the positive electrode and the negative electrode were arranged opposite to each other, leaving one side for sealing. The nonaqueous electrolyte obtained above was injected therein, and after the nonaqueous electrolyte fully penetrated into the diaphragm, etc., it was sealed, pre-charged, and aged to produce a lithium ion secondary battery.
[0384] Industrial Applicability
[0385] The fluororesin film of the present disclosure can be suitably used in a battery exterior body.
Claims
1. A fluororesin film for a battery outer casing, which is a fluororesin film for a battery outer casing composed of a composition containing a fluororesin, characterized in that: After the film was heat treated at 180° C. for 3 minutes, the oxygen ratio of the surface state of one or both surfaces was measured by a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) and was found to be 1.35 atomic % or more. When the film was heat-treated at 180° C. for 10 minutes and then cooled to 25° C. and measured, the absolute values of the dimensional change rates in MD and TD before and after the heat treatment were 2% or less.
2. The fluororesin film for a battery exterior body according to claim 1, wherein The oxygen element ratio is 1.5 atomic % or more. 3 . The fluororesin film for a battery exterior body according to claim 1 , which comprises tetrafluoroethylene-perfluoroalkylvinyl ether (PFA) or tetrafluoroethylene-hexafluoropropylene (FEP).
4. The fluororesin film for a battery exterior body according to any one of claims 1 to 3, wherein The difference between the oxygen element ratio when measuring the surface state of one side or both sides using a scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) and the oxygen element ratio when measuring the film using an argon cluster ion beam at an incident angle of 45° along the depth direction for 15 minutes and the scanning X-ray photoelectron spectroscopy analyzer (XPS / ESCA) is 1.0 atomic % or more.
5. The fluororesin film for a battery exterior body according to any one of claims 1 to 4, wherein When the films are bonded to each other on the same surface at 200° C., the adhesive strength is greater than 30 N / m on only one surface or on both surfaces.
6. The fluororesin film for a battery exterior body according to any one of claims 1 to 5, wherein The bonding strength when the aluminum foil and the fluororesin film are bonded together is 500 N / m or more.
7. The fluororesin film for battery exterior body according to any one of claims 1 to 6, which has an electrolyte permeability of 50 g / m2 2 ·Day or less.
8. A battery outer casing, characterized in that: A method comprising the fluororesin film according to any one of claims 1 to 7 and a metal layer.
9. The battery exterior body according to claim 8, further comprising a layer other than the metal layer and the fluororesin film, The layers other than the metal layer and the fluororesin film are at least one selected from the group consisting of polyethylene, polypropylene, polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether and polybutadiene.
10. The battery housing according to claim 8 or 9, wherein: The fluororesin film is provided on at least one surface in the thickness direction and is present at a position in contact with the electrolyte when the battery is manufactured.
11. The battery exterior body according to any one of claims 8 to 10, wherein The metal layer is aluminum.
12. The battery exterior body according to any one of claims 8 to 11, wherein The bonding strength between the aluminum foil and the fluororesin film is 500 N / mm or more. 13 . A secondary battery comprising the battery housing according to claim 8 and an electrolyte solution.
14. The secondary battery according to claim 13, wherein The fluororesin film of the battery exterior body is present at a position in contact with the electrolyte solution.
Citation Information
Patent Citations
Preparation of tetrafluoroethyleneehexafluoropropylene copolymer
JP1982040847B2
Lithium secondary battery and battery device using it
JP2000268873A
Interphone system
JP2002016712A